Analysis of shear mock-up tests in a canister-clay system for spent nuclear fuel isolation. (December 2022) - Khadivipanah, Peiman; Olivella, Sebastia; Pintado, Xavier; Vaunat, Jean
Abstract: The aim of this paper is to simulate a canister-buffer mock-up test using the finite element computer code CODE_BRIGHT. The response of a copper canister put inside clay barriers that undergo hydration and swelling till complete saturation was investigated. Although the copper is very stiff and resistant and will be emplaced in a clay volume, shear deformations occurring in the clay barrier may have an impact on the canister. A Mock-up test was carried out in a steel cell at a scale of about 1:10 for assessing the consequences of a shear zone for a copper rod that was surrounded by compacted bentonite as a clay barrier. The challenge problem is to perform the simulation of the mock-up tests under the different shear rates that was carried out by Borgesson (1968). The results might contribute to a better understanding of the real shearing response of the system and validate the constitutive models used for the simulations. For this purpose, the mock-up test was simulated with CODE_BRIGHT in hydro-mechanical couplings in three dimensions. For the model validation, the results of the simulations were compared with the test measurements. The constitutive model used for the copper simulation was a viscoplastic model developed by Bodner and Partom. For the bentonite simulation, a viscoplastic model for unsaturated soils based on the Desai and Perzyna theory, using an elliptical yield surface corresponding to the modified Cam-Clay model, was used. Highlights: Verification of viscoplastic constitutive equations of copper (Bodner-Partom model) for copper canister modeling was compared. Hydro-mechanical analysis of canister-clay shear test in mock-up scale was done for 3D modeling in CODE_BRIGHT. Sensitivity analysis of reference model and model calibrated for bentonite have been analysed. Comparison between the calculation of the shearing phase directly and the shearing phase including the saturation phase was done.